2018
DOI: 10.1016/j.epsl.2018.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Authigenic carbonate formation rates in marine sediments and implications for the marine δ13C record

Abstract: Carbon isotope (δ13C) variations measured in carbonates have been attributed to large-scale phenomena throughout Earth history, such as changes in atmospheric oxygen or global glaciations. These interpretations follow from a model wherein the δ13C of marine dissolved inorganic carbon (DIC) is controlled by the relative sedimentary burial rates of biogenic carbonate (BC) and organic carbon (OC). A new model proposes authigenic carbonate (AC) as a third major sedimentary C pool, implying that δ13C anomalies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…The first crucial assumption in the authigenic carbon model (Schrag et al ., ) is that the burial of authigenic carbonate is comparable to organic carbon and marine carbonate fluxes. Accurately estimating this term, however, is difficult: significant authigenic burial fluxes can manifest as subtle changes in bulk geochemistry, and studies targeting pre‐Jurassic periods lack the deep sea sedimentary record which is an important locus of authigenic carbonate burial in the modern ocean (Mitnick et al ., ; Bradbury & Turchyn, ). For this reason, calculating the global authigenic carbon sink from Palaeozoic epicontinental records may represent only a conservative estimate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first crucial assumption in the authigenic carbon model (Schrag et al ., ) is that the burial of authigenic carbonate is comparable to organic carbon and marine carbonate fluxes. Accurately estimating this term, however, is difficult: significant authigenic burial fluxes can manifest as subtle changes in bulk geochemistry, and studies targeting pre‐Jurassic periods lack the deep sea sedimentary record which is an important locus of authigenic carbonate burial in the modern ocean (Mitnick et al ., ; Bradbury & Turchyn, ). For this reason, calculating the global authigenic carbon sink from Palaeozoic epicontinental records may represent only a conservative estimate.…”
Section: Discussionmentioning
confidence: 99%
“…The authigenic carbonate revision of the global carbon cycle model (Schrag et al ., ) was based on observations made from modern sites of authigenesis and assumes that similar processes would have been more prevalent during intervals with low pO 2 , a large dissolved inorganic carbon (DIC) reservoir and reduced biological pump (Higgins et al ., ). Ongoing efforts to measure carbonate authigenesis rates in sea floor sediments (Mitnick et al ., ; Bradbury & Turchyn, ) provide important constraints on modern ƒ AC , but represent an imperfect analogue for Palaeozoic sediments deposited in poorly oxygenated basins prior to the advent of pelagic calcification. Based on modern expectations, the Bakken black shales were deposited in conditions conducive to the formation of isotopically offset authigenic carbonates, but instead host large volumes of disseminated carbonates (7 to 9 wt.%) which are isotopically intermediate ( ε AC ≈ 0·3‰ to 3·7‰).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microfossils in sediments at these sites, as with any sedimentary sequences, have the potential to be influenced by diagenesis. Despite evidence of authigenic carbonate formation, recent modeling work concluded that the influence of dissolution and reprecipitation at Sites 806 and 807 was relatively minor (Mitnick et al, 2018). Prior work has also found minimal impacts on the B/Ca ratio of Pliocene foraminifera from Site 806 (White and Ravelo, 2020) and on the Mg/Ca ratio of Miocene Dentoglobigerina altispera shells at Site 806 (Sosdian et al, 2020).…”
Section: Preservationmentioning
confidence: 99%
“…, contributing to the atmospheric CH 4 -pool and acting as a powerful greenhouse gas (Mitnick et al, 2018). In very shallow waters (<30 m water depth), this aspect is particularly important since gas bubbles can quickly reach the atmosphere (Borges et al, 2016).…”
mentioning
confidence: 99%